A photocurable 3D printed conductive hydrogel sensor and its preparation method

By introducing conductive fillers into flexible wearable sensors and adopting DLP photocuring 3D printing technology, the poor biocompatibility of traditional materials and waste of manufacturing methods is solved, and a conductive hydrogel sensor with high biocompatibility, self-healing and high sensitivity is achieved.

CN116640259BActive Publication Date: 2025-03-04NANJING UNIV OF INFORMATION SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310648947.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-03-04
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

Existing flexible wearable sensor materials have poor biocompatibility, low sensitivity, poor stability, and traditional manufacturing methods lead to waste of materials and inaccurate structure.

Method used

Photocuring 3D printing technology is used to prepare conductive hydrogel sensors. By introducing conductive fillers such as multi-walled carbon nanotubes (MWCNTs) and silver nanowires (AgNWs) into the hydrogel, combined with DLP photocuring 3D printing technology, self-healing, stretchable and high-sensitivity sensors are achieved.

Benefits of technology

It achieves high biocompatibility, self-healing and high sensitivity of materials, reduces material waste, and obtains a high-precision structure through 3D printing technology, suitable for wearable health monitoring devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116640259B_ABST
    Figure CN116640259B_ABST
Patent Text Reader

Abstract

The present invention discloses a photocurable 3D printed self-healing stretchable conductive hydrogel sensor and a preparation method thereof, belonging to the technical field of flexible sensors, the present invention uses poly (N, N-dimethylacrylamide) PDMA-based hydrogel as a matrix material, by adding multi-walled carbon nanotubes and silver nanowires as conductive fillers, this type of filler with high conductivity gives the hydrogel good electrical conductivity, and the sensing performance and mechanical properties of the hydrogel are improved in both directions. Metal ions can form ionic coordination bonds with carboxyl groups in the hydrogel, and PDMA mediates hydrogen bonds and hydrophobic association interactions at the break position of the hydrogel, which accelerates the self-healing ability of the hydrogel sensor. The hydrogel is prepared by a one-pot synthesis, the preparation process is simple, the process parameters are controllable, and the prepared hydrogel can be printed out as a stretchable hydrogel sensor with adjustable structure by DLP photocuring 3D printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible sensors, and in particular relates to a photocurable 3D printed conductive hydrogel sensor and a preparation method thereof. Background Art

[0002] Due to the development of intelligent technology and potential market demand, flexible wearable electronic products have been widely studied. Wearable devices refer to devices that can be worn on different parts of the human body to continuously and in real time obtain physical, chemical, and biomass information, thereby providing services for applications such as health monitoring and medical diagnosis. At present, the main problems in the research of flexible sensors for flexible wearable devices are that the existing sensing material system (silicone, plastic, etc.) has poor biocompatibility, low sensitivity, and poor stability; the traditional manufacturing method causes material waste, cannot accurately control the structure, and has complex processes.

[0003] Hydrogel has a modulus and flexibility similar to that of the skin, allowing it to fit perfectly on human skin; its most important characteristics are high water content and biocompatibility, and water-soluble compounds can diffuse in the polymer network; at the same time, hydrogel also has chemical diversity and adjustable physical properties. The above characteristics far exceed other substrates, so hydrogel is an excellent material for preparing flexible sensors. The introduction of conductive particles multi-walled carbon nanotubes (MWCNT) and silver nanowires (AgNWs), due to their excellent conductivity, can not only improve the mechanical properties and conductive properties of hydrogels, but also effectively improve the sensing performance of hydrogel sensors.

[0004] At the same time, 3D printing technology can realize the miniaturization and personalized preparation of flexible electronic devices, making the sensors have the characteristics of high strength, stretchability, wearability, sensitivity, repeatability and self-healing. Compared with the common fused deposition modeling (FDM) and ink direct writing (DIW), DLP light-curing 3D printing technology has higher precision and faster speed, and the results are expected to have great application potential in flexible wearable sensors. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a photocurable 3D printed self-healing stretchable conductive hydrogel sensor and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A photocurable 3D printed conductive hydrogel sensor and a preparation method thereof, comprising the following steps:

[0008] MWCNT dispersion or AgNWs dispersion is added to deionized water to obtain nanofiller aqueous solutions of different concentrations, ammonium dodecyl sulfate and sodium chloride are added to the aqueous solution containing the nanofiller, and after dissolution, monomers and cross-linking agents are introduced in sequence, heated and stirred to obtain a hydrogel solution;

[0009] Adding an accelerator, an initiator and a dye to a hydrogel solution, and stirring to obtain a hydrogel ink;

[0010] The above hydrogel ink is used for photocuring 3D printing to obtain a fibrous hydrogel sensor.

[0011] Furthermore, the MWCNT dispersion preparation method is to disperse MWCNT powder in deionized water.

[0012] Furthermore, the concentration of MWCNT in the MWCNT dispersion is 0-1% (w / v), the diameter of AgNWs in the AgNWs dispersion is 100-200 nm, the length is 30-80 μm, and the concentration is 10 mg / mL.

[0013] Furthermore, the concentration of MWCNT in the nanofiller aqueous solution containing MWCNT is 0-0.67% (w / v), and the concentration of AgNWs in the nanofiller aqueous solution containing AgNWs is 0-0.67% (w / v).

[0014] Furthermore, the monomer is octadecyl methacrylate and the cross-linking agent is NN dimethyl acrylamide.

[0015] Furthermore, the accelerator is tetramethylethylenediamine, the initiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and the dye is lemon yellow.

[0016] Furthermore, the ammonium dodecyl sulfate and sodium chloride are added to the aqueous solution containing the nanofiller and then heated in a water bath.

[0017] Furthermore, the parameters of the light-curing 3D printing are light intensity 15-18W / cm 3 , exposure time 18-25s, number of base layers 2-5, base exposure time 25-28s, platform temperature 27℃, trough temperature 27-50℃.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention uses DLP light-curing 3D printing technology to prepare nanocomposite hydrogel sensors. Compared with traditional manufacturing technologies, 3D printing technology, as a new form of additive manufacturing, can effectively reduce material waste. At the same time, the production process is simple and the technical requirements for operators are relatively low. Compared with traditional 3D printing technologies such as FDM and DIW, DLP has more advantages in design accuracy and freedom. It can customize complex models and achieve higher-precision printing;

[0020] (2) The hydrogel raw material used in the present invention is a three-dimensional hydrophilic polymer network that can swell to the maximum extent in the aqueous phase, similar to the natural extracellular matrix, and has very good biocompatibility. Secondly, by adding two nano-conductive fillers, AgNWs and MWCNT, a good conductive network can be formed, so that the designed and prepared hydrogel system has self-healing and high tensile properties, as well as high conductivity, sensitivity, moisture retention, transparency and other properties, which can simultaneously meet the multiple requirements of electronic skin for wearable devices;

[0021] (3) With the help of 3D printing technology, the miniaturization and personalized preparation of hydrogel-based flexible electronic devices can be achieved in the present invention. The sensitivity of the sensor can be further improved through structural design engineering, so that the obtained conductive hydrogel flexible sensor has great potential in human health monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 is a photograph of the hydrogel prepared by the present invention being 3D printed by a DLP light-curing printer;

[0024] Figure 2 is a scanning electron microscope photograph of the hydrogel sensor prepared in Example 1 of the present invention;

[0025] Figure 3 Schematic diagram of the self-healing performance of the hydrogel material prepared in Example 1 of the present invention

[0026] Figure 4 is a graph showing the mechanical properties of four hydrogel sensors with different water contents in Example 1 of the present invention;

[0027] Figure 5This is a mechanical property test diagram of three hydrogel sensors containing different concentrations of CNTs prepared in Example 2 of the present invention compared with a hydrogel sensor without conductive fillers;

[0028] Figure 6 This is a sensing performance test diagram of three hydrogel sensors containing different concentrations of CNTs prepared in Example 2 of the present invention compared with a hydrogel sensor without conductive fillers;

[0029] Figure 7 This is a mechanical property test diagram of the hydrogel sensors with three different concentrations of AgNWs prepared in Example 3 of the present invention;

[0030] Figure 8 3 is a test diagram of the conductivity of the hydrogel sensor prepared in Examples 1 and 3 of the present invention;

[0031] Fig. 9 is a comparison chart of the sensing performance of the hydrogel sensors prepared in Examples 1 and 3 of the present invention;

[0032] Fig.10 This is a cyclic stretch test diagram of the hydrogel sensor prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A photocurable 3D printed self-healing stretchable hydrogel sensor and a preparation method thereof, comprising the following steps: selecting a photocrosslinking system hydrogel with NN dimethyl acrylamide (DMA) as a crosslinker, octadecyl methacrylate (SMA) as a monomer, and phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP) as an initiator, introducing micelles in an ADS-NaCl aqueous solution into DMA and SMA, and crosslinking to form a PDMA hydrogel sensor under 405nm ultraviolet light by using DLP photocurable 3D printing technology through the action of the LAP initiator. By changing the water content to explore its effect on the ultraviolet light crosslinking process, two commonly used conductive fillers, multi-walled carbon nanotubes (MWCNT) and silver nanowires (AgNWs), are doped in the hydrogel system in turn, making full use of the synergistic effect of MWCNT, AgNWs and hydrogel matrix, improving the conductivity and sensitivity of the PDMA-based hydrogel sensor, and further expanding the multifunctionality of the hydrogel. The obtained composite was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The mechanical properties of the material were tested using a flexible electronic tester, and the sensing performance, i.e. sensitivity, of the material was tested by connecting it to a digital source meter, and its influence on the 3D printing precursor ink was systematically explored.

[0035] The specific steps include:

[0036] Step 1: Preparation of hydrogel precursor solution

[0037] (1) Preparation of MWCNT and AgNWs dispersions: Take an appropriate amount of MWCNT powder and disperse it in deionized water. Ultrasonic dispersion is used to obtain a uniformly dispersed MWCNT dispersion. The AgNWs dispersion is shaken evenly. The concentration of multi-walled carbon nanotubes (MWCNT) is 0-1% (w / v), the ultrasonic time is 1 h, the diameter of silver nanowires (AgNWs) is 100-200 nm, the length is 30-80 μm, and the concentration is 10 mg / mL.

[0038] (2) Preparation of hydrogel solution: Take an appropriate amount of MWCNT dispersion or AgNWs dispersion in deionized water to obtain nanofiller aqueous solutions of different concentrations, add ammonium dodecyl sulfate (ADS) and sodium chloride (NaCl) to the aqueous solution containing the nanofiller, heat it in a water bath and dissolve it, introduce the monomer and the cross-linking agent in turn, heat it in a water bath and stir to obtain a hydrogel solution, wherein the volume of deionized water is 3-15 mL, the final MWCNT aqueous solution concentration is 0-0.67% (w / v), the AgNWs aqueous solution concentration is 0-0.67% (w / v), the selected monomer is octadecyl methacrylate (SMA), and the cross-linking agent is NN dimethyl acrylamide (DMA).

[0039] (3) Preparation of photocurable 3D printing hydrogel ink: Based on step 1 (2), an accelerator, an initiator and a dye are sequentially added to the hydrogel solution and stirred evenly to obtain a photocurable 3D printing hydrogel ink. The selected accelerator is tetramethylethylenediamine (TEMED), the initiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP), and the dye is lemon yellow.

[0040] Step 2: Preparation of 3D printed hydrogel sensors

[0041] The three-dimensional digital model of the sensor was designed using Sketch UP 3D modeling software, exported as an STL file, and imported into a DLP digital light processing (photocuring) 3D printer with a 405nm ultraviolet light source. The model was sliced ​​by the printer's attached software. The hydrogel precursor solution obtained in step 1 was poured into the material tank, and by adjusting the exposure intensity, exposure time, platform temperature and other printing parameters, a high-precision, structured fibrous hydrogel sensor was printed.

[0042] Step 3: Testing of mechanical and sensing properties of hydrogel sensors

[0043] According to the size of the tensile gauge fixture, a three-dimensional model of the standard spline for the hydrogel sensor tensile test was designed, and the hydrogel was printed into a standard spline using DLP light-curing 3D printing. The tensile properties of the self-healing stretchable hydrogel sensor were tested using a flexible electronic tester, and the sensor was connected to a digital source meter to test the material's sensing performance, i.e. sensitivity, through resistance changes.

[0044] In step 2, the three-dimensional model parameters of the hydrogel sensor are 1mm×1mm×40mm, and the printing parameters in the DLP light-curing 3D printing process are shown in the following table:

[0045]

[0046] In step three, the standard specimen model for the hydrogel tensile test is 1 mm × 10 mm × 40 mm, and the tensile speed of the flexible electronics tester is 1 mm / s.

[0047] Example 1

[0048] (1) Preparation of hydrogel precursor solution

[0049] First, 2.1 g ADS and 0.8772 g NaCl were added to 15 mL, 10 mL, 7.5 mL, and 5 mL deionized water, respectively, and heated in a water bath at 35 °C and dissolved. Then, 0.2847 g SMA was introduced as a monomer in sequence. After heating in a water bath for 2 h, 4.4 mL of cross-linking agent DMA was added, and the water bath was continued to be heated and stirred for 1 h to obtain a hydrogel precursor solution. Further, 75 μL TEMED accelerator, 25 mg LAP initiator, and 5 mg lemon yellow dye were added to the hydrogel solution and stirred evenly to obtain a hydrogel ink that can be photocured for 3D printing.

[0050] (2) Preparation of 3D printed hydrogel sensors

[0051] The 3D digital model of the sensor with the size of 1mm×1mm×40mm was designed using Sketch UP 3D modeling software, exported as an STL file, and imported into a DLP digital light processing (photocuring) 3D printer with a 405nm ultraviolet light source. The model was sliced ​​by the printer's attached software. The hydrogel ink obtained in step (1) was poured into the material tank, and the high-precision, structured fibrous hydrogel sensor was printed by adjusting the printing parameters such as exposure intensity, exposure time, and platform temperature. The printing parameters are shown in the following table:

[0052]

[0053] Figure 1 a and b are photos of the hydrogel prepared by the present invention being 3D printed by a DLP light-curing printer, which can print flat and complex three-dimensional structures, proving that the hydrogel ink manufactured by this invention can realize DLP 3D printing. Figure 2 is a SEM image of the hydrogel sensor. The hydrogel as a whole presents a relatively uniform micron-scale network structure. At the same time, the hydrogels prepared in the above steps are cut and placed together, as shown in FIG. Figure 3 As shown, after 5 minutes, it can be observed that the hydrogels on both sides begin to reconnect together, the cracks gradually decrease, and after 30 minutes, they are basically completely connected together, and will not crack again during stretching operations, indicating that the hydrogel material prepared by the present invention can achieve the function of self-healing.

[0054] (3) Testing of mechanical and sensing properties of hydrogel sensors

[0055] According to the size of the tensile gauge fixture, a three-dimensional digital model of the standard specimen for the hydrogel sensor tensile test was designed, with a size of 1mm×10mm×40mm. The hydrogel was printed into a standard specimen using DLP light-curing 3D printing. The tensile properties of the self-healing stretchable hydrogel sensor were tested using a flexible electronic tester with a tensile speed of 1mm / s. The sensor was then connected to a digital source meter to test the material's sensing performance, i.e. sensitivity, through resistance changes. Figure 4 This is a mechanical property test diagram of four hydrogel sensors with different water contents in Example 1, i.e., a stress-strain curve. It can be seen that the DLP-type 3D printed hydrogel provided by the present invention has good mechanical properties, and as the water content decreases, the tensile strength at break of the hydrogel sensor is greatly improved, and its compressive strength can reach up to 250KPa, but it still retains a wider tensile range, and the elongation at break can reach 1650%.

[0056] Example 2

[0057] (1) Preparation of hydrogel precursor solution

[0058] First, 1 mg, 5 mg, and 10 mg of MWCNT powder were dispersed in 1 mL of deionized water and ultrasonically dispersed to obtain a uniformly dispersed MWCNT dispersion; 1 mL of MWCNT dispersion of different concentrations was taken in 14 mL of deionized water and shaken evenly to obtain 0.06% (w / v), 0.34% (w / v), and 0.67% (w / v) MWCNT aqueous solutions, 2.1 g of ADS and 0.8772 g of NaCl were added to the solution, heated in a water bath at 35°C and dissolved, 0.2847 g of SMA was introduced as a monomer, and 4.4 mL of crosslinker DMA was added after heating in a water bath for 2 h. The water bath was continued to be heated and stirred for 1 h to obtain a hydrogel precursor solution; 75 μL of TEMED accelerator, 25 mg of LAP initiator, and 5 mg of lemon yellow dye were further added to the hydrogel solution to stir it evenly to obtain a hydrogel ink that can be photocured for 3D printing.

[0059] (2) Preparation of 3D printed hydrogel sensors

[0060] The 3D digital model of the sensor with the size of 1mm×1mm×40mm was designed using Sketch UP 3D modeling software, exported as an STL file, and imported into a DLP digital light processing (photocuring) 3D printer with a 405nm ultraviolet light source. The model was sliced ​​by the printer's attached software. The hydrogel ink obtained in step (1) was poured into the material tank, and the high-precision, structured fibrous hydrogel sensor was printed by adjusting the printing parameters such as exposure intensity, exposure time, and platform temperature. The printing parameters are shown in the following table:

[0061]

[0062] (3) Testing of mechanical and sensing properties of hydrogel sensors

[0063] According to the size of the tensile gauge fixture, a three-dimensional digital model of the standard specimen for the hydrogel sensor tensile test was designed, with a size of 1mm×10mm×40mm. The hydrogel was printed into a standard specimen using DLP light-curing 3D printing. The tensile properties of the self-healing stretchable hydrogel sensor were tested using a flexible electronic tester with a tensile speed of 1mm / s. The sensor was then connected to a digital source meter to test the material's sensing performance, i.e. sensitivity, through resistance changes. Figure 5 , 6 The figures are respectively the test graphs of the mechanical properties and sensing properties of the hydrogel after adding different contents of MWCNT. It can be seen from the figures that with the increase of the content of the conductive filler MWCNT, the mechanical properties and sensing properties of the hydrogel sensor prepared by the present invention are improved. When the content of the added MWCNT is 0.67% (w / v), the compressive strength can reach 13KPa, and the elongation at break can reach 480%. Secondly, the sensitivity factor calculated according to its resistance change rate and strain also increases from 0.05 to 0.25, showing a 5-fold increase.

[0064] Example 3

[0065] (1) Preparation of hydrogel precursor solution

[0066] First, a 10 mg / ml AgNWs dispersion and deionized water were added to a beaker in the following volumes of 0.5 mL: 2.5 mL, 1 mL: 2 mL, and 2 mL: 1 mL, respectively, and shaken evenly to obtain three concentrations of AgNWs aqueous solutions of 0.16% (w / v), 0.34% (w / v), and 0.67% (w / v). 2.1 g ADS and 0.8772 g NaCl were added to the solution, heated in a water bath at 35 °C and dissolved, and 0.2847 g SMA was introduced as a monomer in turn. After heating in a water bath for 2 h, 4.4 mL of cross-linking agent DMA was added, and the water bath was continued to be heated and stirred for 1 h to obtain a hydrogel precursor solution. 75 μL TEMED accelerator, 25 mg LAP initiator, and 5 mg lemon yellow dye were further added to the hydrogel solution and stirred evenly to obtain a hydrogel ink that can be photocured for 3D printing.

[0067] (2) Preparation of 3D printed hydrogel sensors

[0068] The 3D digital model of the sensor with the size of 1mm×1mm×40mm was designed using Sketch UP 3D modeling software, exported as an STL file, and imported into a DLP digital light processing (photocuring) 3D printer with a 405nm ultraviolet light source. The model was sliced ​​by the printer's attached software. The hydrogel ink obtained in step (1) was poured into the material tank, and the high-precision, structured fibrous hydrogel sensor was printed by adjusting the printing parameters such as exposure intensity, exposure time, and platform temperature. The printing parameters are shown in the following table:

[0069]

[0070] (3) Testing of mechanical and sensing properties of hydrogel sensors

[0071] According to the size of the tensile gauge fixture, a three-dimensional digital model of the standard sample bar for the stretch test of the hydrogel sensor is designed, and its size is 1mm×10mm×40mm. The hydrogel is printed into a standard sample bar using DLP light-curing 3D printing. The tensile performance of the self-healing stretchable hydrogel sensor is tested using a flexible electronic tester with a stretching speed of 1mm / s, and connected to a digital source meter to test the sensing performance of the material, i.e., sensitivity, through resistance change. With the increase of the content of the conductive filler AgNWs, the mechanical properties and sensing performance of the hydrogel sensor prepared by the present invention are improved. Figure 7 It can be seen that when the content of AgNWs is 0.67% (w / v), the compressive strength can reach 800KPa and the elongation at break can reach 1600%. Figure 8 The impedance diagram of the hydrogel sensors prepared in Examples 1 and 3 is 4Ω and 15.5Ω respectively, but the cross-section and conduction distance of the two samples are inconsistent. According to the conductivity calculation formula, the ionic conductivity of the hydrogel sensor after adding AgNWs increases from 2.65S / m to 41.07S / m compared with the hydrogel in Example 1, which has good conductivity. Fig. 9 The resistance change rate and strain range in the sensing performance test diagram are calculated, and it is found that the sensitivity factor of this embodiment can reach 3, which is 12 times that of the sensor prepared in Example 2. This further shows that the addition of conductive nanofiller AgNWs can improve the sensing performance of the hydrogel sensor and prepare a highly sensitive sensor device. Fig.10 The cyclic tensile test of the hydrogel sensor prepared in this example shows that the resistance change rate is basically stable at about 100% in the 10-100s tensile test, indicating that the hydrogel prepared by the invention has a certain cyclic stability after adding the conductive filler AgNWs.

[0072] In summary, the photocurable 3D printed self-healing stretchable hydrogel sensor and its preparation method provided by the present invention can be found through the above examples that reducing the water content of the hydrogel can effectively improve the mechanical properties of the hydrogel, namely the tensile strength; by adding two commonly used conductive fillers, multi-walled carbon nanotubes (MWCNT) and silver nanowires (AgNWs), the mechanical properties of the hydrogel sensor are effectively improved, and the conductivity and sensitivity of the PDMA-based hydrogel are improved. The designed flexible hydrogel sensor structure can be obtained in the form of DLP photocurable 3D printing, and the sensor device can be designed with different diameters and double-sided attached microbeads to improve the rapid response time and degree of the device when it is subjected to changes such as pressure and tension, and further improve the device sensitivity. 3D printing is used to design a sensor model that conforms to human mechanics and morphology, so that it can fit closely with the human body and can follow the changes in human morphology when the joints are bent and moved. The results are expected to have great application potential in flexible wearable sensors.

[0073] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0074] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a photocurable 3D printed conductive hydrogel sensor, characterized in that: The following steps are involved: A photo-crosslinking system hydrogel was selected with NN dimethyl acrylamide as a crosslinker, octadecyl methacrylate as a monomer, and phenyl-2,4,6-trimethylbenzoyl lithium phosphite as an initiator. Micelle in an aqueous solution of ammonium dodecyl sulfate-sodium chloride was introduced into NN dimethyl acrylamide and octadecyl methacrylate. Through the action of phenyl-2,4,6-trimethylbenzoyl lithium phosphite initiator, DLP photocuring 3D printing technology was used to crosslink under 405nm ultraviolet light to form a hydrogel sensor. The AgNWs dispersion was dissolved in deionized water to obtain aqueous solutions of nanofillers with different concentrations, ammonium dodecyl sulfate and sodium chloride were added to the aqueous solution containing the nanofillers, and after dissolution, monomers and cross-linking agents were introduced in sequence, heated and stirred to obtain a hydrogel solution; Adding an accelerator, an initiator and a dye to a hydrogel solution, and stirring to obtain a hydrogel ink; Perform photocuring 3D printing using the hydrogel ink to obtain a fibrous hydrogel sensor; The AgNWs concentration in the AgNWs-containing nanofiller aqueous solution is 0-0.67% w / v and is not 0.

2. The method for preparing a photocurable 3D printed conductive hydrogel sensor according to claim 1, characterized in that: The diameter of AgNWs in the AgNWs dispersion is 100-200 nm, the length is 30-80 μm, and the concentration is 10 mg / mL.

3. The method for preparing a photocurable 3D printed conductive hydrogel sensor according to claim 1, characterized in that: The accelerator is tetramethylethylenediamine, the initiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and the dye is lemon yellow.

4. The method for preparing a photocurable 3D printed conductive hydrogel sensor according to claim 1, characterized in that: After the ammonium dodecyl sulfate and sodium chloride are added into the aqueous solution containing the nanofiller, the solution needs to be heated in a water bath.

5. The method for preparing a photocurable 3D printed conductive hydrogel sensor according to claim 1, characterized in that: The parameters of the light-curing 3D printing are light intensity of 15-18 W / cm3, exposure time of 18-25 s, number of base layers of 2-5, base exposure time of 25-28 s, platform temperature of 27°C, and material tank temperature of 27-50°C.

6. The hydrogel sensor prepared by the method according to any one of claims 1 to 5.

7. Application of the hydrogel sensor according to claim 6 in the field of flexible sensors.

Citation Information

Patent Citations

  • Color self-healing intelligent hydrogel and preparation method thereof

    CN110343266A

  • Conductive resin for 3D printing technology, and preparation method and application thereof

    CN113956409A